Revisiting the region of the Open Cluster NGC 5606 - Orsatti, Ana Maria (2007)
We present polarimetric observations in the UBVRI bands corresponding to 54 stars located in the direction of the NGC 5606. Our intention is to analyze the dust characteristics between the Sun and the cluster, as well as to confirm doubtful memberships using polarimetric tools. We also want to determine if a group of 11 B and A stars identified in the past by Vazquez & Feinstein (1991, A&AS, 87,383) in front of NGC 5606 has any physical entity. From polarimetric data their local magnetic field with an orientation which is close to the direction of the Galactic Plane (Theta= 70 degree), but the direction of the polarimetric vector for the members of the cluster seems to be lower than this value. NGC 5606 can be polarimetrically characterized with Pmax= 2.97% and Theta_v=63.5 degree. The internal dispersion of the polarization values for the members of NGC 5606 seems to be compatible with intracluster dust. We were able to add four possible new members to the list of stars in NGC 5606, and to reject other accepted as members in past investigation; and we identify 17 (out of the 54 observed stars) with intrinsic polarization in their light. The group of late B- and A-type stars could be physically related, with characteristics of an open cluster of intermediate age (between 0.79 and 1. x 10 8 yr). For this group we obtained representative values of P= 2.12% and theta_v= 70.9 degree. The new cluster, which we have provisionally named Anon (La Plata 1), extends from NE to SW across the face of NGC 5606 corering about 10´. The fitting procedure of Schmidt-Kaler´s ZAMS (1982, in Landolt/Bornstein, Neue Series VI/2b) was used to derive the distance to the group is E_(B-V)=0.27+/-0.08 mag and the dust distribution shows great variability across its face. We think that the small open cluster has gone undetected due to the lack of bright member stars in it.